MANAJEMEN KONFLIK BIDANG TRANSPORTASI DI KOTA PEKANBARU (STUDI KASUS TAKSI KONVENSIONAL DENGAN ANGKUTAN ONLINE) - Putri, Nadya Maharani; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Transportation Conflict Management in the City of Pekanbaru (Case Study of Conventional Taxi with Online Transportation) is an effort to resolve conflicts carried out by related parties in this case conventional taxi drivers and online transport drivers to get a solution to the conflict between the two organizations. This study aims to determine conflict management in the transportation sector in the city of Pekanbaru (a case study of a conventional taxi with online transportation) and factors that hinder the conflict management of conventional taxis with online transportation in the city of Pekanbaru. The focus of the study in this study is the management of conflict between conventional taxis and online transportation in the city of Pekanbaru. Informants in the study were the Head / Staff of the Land Transportation Sector, Head / Staff of Transportation in the City of Pekanbaru Transportation Service, online transport drivers, and conventional taxi drivers. The research method used is descriptive qualitative data collection techniques are interviews. The results showed that the Riau Province Transportation Agency in resolving conflicts that occurred between conventional taxis and online transportation had not been maximized. This is because there are still online transportation operating even though they do not have licenses in accordance with Minister of Transportation Regulation No.108 of 2017 so that conventional taxis that already have permits feel they do not get justice from the government, this is the main cause of conflicts between conventional taxis and transportation on line. The Riau Province Transportation Agency is also unable to facilitate the two parties in conflict to mediate that has been directly requested by the conflicting parties so that the two conflicting parties can express their wishes and find a solution to the conflict between them. Factors influencing Conflict Management in Transportation in the City of Pekanbaru (Case Study of Conventional Taxi with Online Transport) include Competition and Regulations that are not implemented. Keywords: Conflict Management, Conventional Cab, Transport Online